Effect of Different Surface Modifications of Acrylic Teeth and Thermocycling on Shear Bond Strength to Polycarbonate Denture Base Material - Al-Somaiday, Humam M.; Rafeeq, Aula Kamal; Al-Samaray, Manar E. (International Journal of Biomaterials, 2022)
During prosthodontic clinical practice, the most commonly reported type of failure is the debonding of teeth to the denture base. Incompatible surface conditions at the tooth/denture base interface result in a lack of bonding. This study aimed to study the influence of different surface modifications of acrylic teeth and thermocycling on shear bond strength to polycarbonate denture base material. Eighty cylinder-shaped samples were fabricated. The tested samples were divided into 4 groups (n = 20). Group A represents the control group, group B represents the mechanical modification of the tooth, while group C and group D represent the chemical treatment of the tooth with ethyl acetate and bonding agent, respectively. Each group was further subdivided into 2 categories depending on the thermocycling procedure (N = 10). All samples were tested for shear bond strength tests. A computer-controlled universal testing machine performed the shear bond test at a 0.5 mm/min crosshead speed. Three-way ANOVA (P=0.05) was used for the statistical analysis of the data. Results show that shear bond strength was significantly affected by the surface treatment, whether it is mechanical or chemical (P≤0.01) (B > D > C) compared with a control group (A). However, thermocycling has a nonsignificant decrease in the bond strength values in all experimental groups (P>0.05) (B > D > C > A). The mechanical treatment by creating retentive holes (B) provides better results than the chemical surface treatment with a bonding agent and ethyl acetate (D and C, respectively). This study concluded that various surface conditioning methods affect the bonding strength of acrylic teeth and polycarbonate denture base material with no effect of thermocycling.